Institutionalization of Media Market in Greek Political System - Knopek, Jacek (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2022)
The article points to the process of the institutionalization of the Greek media market. This process began to take shape after the country’s accession to the European structures, i.e. after 1981. Successively since the late 1980s, it has been shaped based on new initiatives, forms and activities. However, this process is not yet completed due to the changes that have taken place over the last decade. At that time, the members of the National Broadcasting Council, for procedural reasons related to the mode of appointment to this Council, were unable to grant or renew broadcasting licences, which led to a media crisis. In addition, the Greek state was on the brink of solvency due to the condition of its finances. The new government created another media related institution, this time the General Secretariat for Information and Communication, which reported directly to the Prime Minister, and its aim was to control the press, radio and television market. Apart from the leading institutions, supporting bodies are also responsible for the Greek media market. To a large extent, they (such as ministries or central offices like the Telecommunications and Postal Commission) existed much earlier and some media powers were handed over to them to assist the leading institutions in fulfilling their functions. Outside of this area, there was content disseminated on the Internet, which came under the control of a special unit established within the police structures.

W artykule wskazuje się na proces instytucjonalizacji greckiego rynku medialnego. Proces ten zaczął kształtować się po wstąpieniu tego kraju do struktur europejskich, czyli po 1981 r. Sukcesywnie od końca lat 80. XX w. kształtował się on w oparciu o nowe inicjatywy, formy i działania. Jednakże proces ten jeszcze się nie zakończył ze względu na zmiany, do jakich doszło w ostatnim dziesięcioleciu. W tym czasie członkowie Krajowej Rady Radiofonii i Telewizji, ze względów proceduralnych związanych z trybem powoływania tego gremium, nie byli w stanie rozdzielać ani przedłużać koncesji radiowo-telewizyjnych, co wywołało kryzys medialny. Dodatkowo państwo greckie stanęło na krawędzi wypłacalności ze względu na stan jego finansów. Nowy rząd stworzył kolejną instytucję medialną, tym razem Sekretariat Generalny ds. Informacji i Komunikacji, który podlegał bezpośrednio premierowi i miał kontrolować rynek prasowo-radiowo-telewizyjny. Poza instytucjami wiodącymi za grecki rynek mediów odpowiadają także gremia wspomagające. W dużej mierze istniały one (jak ministerstwa czy urzędy centralne typu komisja telekomunikacji i poczty) znacznie wcześniej i do ich kompetencji oddano niektóre uprawnienia medialne, które pomagać miały instytucjom wiodącym w wypełnianiu swoich funkcji. Poza tym obszarem występowały treści upowszechniane w internecie, które znalazły się pod kontrolą specjalnej jednostki powołanej w ramach struktur policyjnych.
Instytucjonalizacja rynku medialnego w greckim systemie politycznym
Keywords: Greece; political system; political institutions; media; media system; Grecja; system polityczny; instytucje polityczne; media; system medialny